Kinesio Taping decreases healing area and modulates the tissue architecture on the cutaneous wound (Research, Society and Development, 2021)
The skin is an organ that promotes elasticity and also resistance against mechanical forces. After injury, its organization is altered by the repair process, compromising the physiological mechanical conditions of the skin. In this context, it has been demonstrated that Kinesio Taping (KT) accelerates the cicatricial process and prevents the development of skin adhesions, but other actions of this method in the cutaneous repair tissue remain indeterminate. Objective: To investigate the histological effects of KT in tissue repair of cutaneous wound. Methods: The procedure involved the preparation and suturing of an incisional wound of 5 cm in length on the epilated back of Wistar rats. After ten days, KT was applied with different stretch levels - 0, 20, 40, 60, 80 and 100% - for six hours. The skin fragment corresponding to the scar was collected and analysed by histological procedures. Results: KT decreased repair tissue area, regardless of the degree of strain, while mast cells activity was not affected by the treatment. 80% stretched KT increased the vascular density of repair tissue. Also, there was a predominance of type III collagen fibers over type I in all groups treated with KT and modulation in tissue architecture in GKT100.